Pic-tac-tell como una estrategia de aprendizaje cooperativo para desarrollar habilidades de escritura del idioma extranjero inglés entre los estudiantes del décimo año en el colegio Pío Jaramillo Alvarado. Período académico 2014-2015 - Medina Andrade, Sisa Curi (2016)
This action research study was focused on the use of the Pic-Tac-Tell as a cooperative learning strategy to develop writing skills with tenth-grade students at Pio Jaramillo Alvarado high school. The objective of this research was to improve writing skills because the students showed a low level on writing skills. The researcher made observations in which allowed her to design an intervention plan that helped to make a pretest and a pre questionnaire that were useful to measure their knowledge on writing skills and their cooperative work in classroom . Consequently, the results of the posttest and post questionnaire revealed a good progress on writing skills and their excellent cooperative work in classroom. Therefore, the Pic-Tac-Tell strategy is important and interesting because students can develop their ability to write in order to improve it, and to work cooperatively in classroom is necessary to use suitable techniques in order to get students motivate to work in a good environment